Estimates of Dietary Exposure to Antibiotics among a Community Population in East China - Yingying Wang; Xinping Zhao; Jinxin Zang; Yurong Li; Xiaolian Dong; Feng Jiang; Na Wang; Lufang Jiang; Qingwu Jiang; Chaowei Fu (MDPI AG, 2022)
Background: Antibiotics are widely used in clinics, livestock farms and the aquaculture industry. A variety of antibiotics in foods and drinking water may lead to important and inadvertent dietary exposure However, the profile of dietary exposure to antibiotics in humans is not well-explored. East China is an economically developed area with a high usage of antibiotics and a high rate of antibiotic resistance (ABR). This study aimed to evaluate the total intake level of antibiotics in humans via foods and drinking water based on a community population in East China. Methods: A total of 600 local residents from 194 households were recruited into this study in Deqing County of Zhejiang Province since June 2019. Each subject was asked to fill a food frequency questionnaire to report their daily consumption of foods and drinking water. Tap water samples were collected from ten households and twenty-one antibiotics of five categories were selected to detect in drinking water. Data of antibiotic residues in animal-derived foods were obtained from the notification of unqualified edible agricultural products after special supervision sampling inspection in Deqing County. The human dietary exposure to antibiotics was estimated by combining the data of antibiotic contamination in foods and drinking water, and the information of dietary consumption. Results: Of twenty-one antibiotics selected, subjects were exposed to a total of sixteen antibiotics, ranging from 15.12 to 1128 μg/day via two main dietary routes (animal-derived foods and drinking water). The overall dietary exposure level varied greatly in the antibiotics detected and their sources. Compared with other antibiotics, enrofloxacin made the most contributions in terms of dietary exposure, with a median exposure level of 120.19 μg/day (IQR: 8.39-698.78 μg/day), followed by sulfamethazine (median: 32.95 μg/day, IQR: 2.77-162.55 μg/day) and oxytetracycline (median: 28.50 μg/day, IQR: 2.22-146.58 μg/day). The estimated exposure level via drinking water (at the ng/day level, median: 26.74 ng/day, IQR: 16.05-37.44 ng/day) was significantly and substantially lower than those via animal-derived foods (at the μg/day level, median: 216.38 μg/day, IQR: 87.52-323.00 μg/day). The overall dietary exposure level also showed differences in sex and age. Males and youths were more likely to be exposed to antibiotics via dietary routes than others. Conclusions: The community population investigated in East China was extensively exposed to multiple antibiotics via dietary routes. Long-term exposure to low-dose antibiotics in animal-derived foods was the primary dietary exposure route, compared with drinking water. Enrofloxacin contributed to the major body burden of dietary exposure, based on the combination of consumption of aquatic products and considerable enrofloxacin residues in them. Although the human dietary exposure level to antibiotics via drinking water and animal-derived foods ranged from ng/day to μg/L, their chronic toxicity and the accumulation and spread of ABR may be potential hazards to humans. Therefore, long-term monitoring of antibiotic contaminations in foods and drinking water, and human dietary antibiotic exposure is warranted.